The Geography of Welfare in Benin, Burkina Faso, Côte d'Ivoire, and Togo - Nguyen, Nga Thi Viet; Dizon, Felipe F. (World Bank, Washington, DC, 2017)
This report aims to assess the spatial disparities in economic development along four important dimensions: (i) It provides stylized facts of the underlying forces behind within-country inequality, namely natural endowment, agglomeration economies, and market access. These are the three building blocks of the economic geography literature; (ii) It examines spatial disparities in welfare and poverty. As the agricultural sector is a cornerstone of the economy in this sub-region, the report explores geographical differences in agricultural activity; (iii) It quantifies the roles of natural endowment, agglomeration economies, and market access in determining the spatial distribution of welfare and agricultural productivity; (iv) It suggests a number of policy guidelines that may help improve shared prosperity across space.